Dampak React Berbantuan E-modul Terhadap Kemampuan Berpikir Reflektif Dan Kemampuan Numerik - Sarum, Lia; Farida; Andriani, Siska (Universitas Pekalongan, 2025)
Reflective thinking ability is the ability to make connections between new information and previous information to solve problems by drawing conclusions. Meanwhile, numerical ability is the ability to calculate. Both are very important for students in studying mathematics. Based on the results of pre-research test instruments conducted in class X SMA Negeri 1 Sukau West Lampung, data obtained that reflective thinking ability and numerical ability are still relatively low. This is due to the choice of learning strategies which are still monotonous. Therefore, researchers are interested in implementing the REACT (Relating, Experiencing, Applying, Cooperative, Transferring) Learning Strategy Assisted by E-Modules on Students' Reflective Thinking and Numerical Abilities. The population in this study were all class X students at SMA Negeri 1 Sukau, while the samples were students from classes X C, X D, and X F. Class X C is experimental class 1, class X D is experimental class 2, and class X F is the control class. This research uses a quantitative approach in this research using Quasi Experiment Design. The sampling technique is Cluster Random Sampling. In this research, the data collection techniques are observation, documentation and tests. The data analysis used was Multivariate Analysis of Variance (MANOVA) with a significance level of 5%. Based on the results of MANOVA research, it shows that the REACT (Relating, Experiencing, Applying, Cooperative, Transferring) learning strategy assisted by e-modules has an impact on students' reflective thinking abilities and numerical abilities.